Implementation of the Pancasila Learner Profile Strengthening Project at SDN 183/II Sumber Mulya Movement School - Rizki, Putri Nabila; Safitri, Desy Widya; Hadi, Muhamad Sofian (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research was motivated by a lack of understanding by educators in designing P5 plans due to a lack of training attended by educators and a lack of guidance to fellow educators after attending workshops. There is no involvement of Pancasila students in determining or choosing the themes and topics to be chosen. This research aims to describe the experience of the facilitator team in implementing, obstacles and efforts to overcome obstacles to the project to strengthen the profile of Pancasila students at the driving school SDN 183/II Sumber Mulya. This research method uses a qualitative phenomenological method, this research was carried out at SDN 183/II Sumber Mulya. Participants in the research were the team of facilitators for phases A, B, C, class VI homeroom teachers, PAI teachers and Pancasila students for phases A, B and C. Data collection techniques were carried out using interviews, observation and documentation. Data analysis techniques were carried out using triangulation and the ATLAS TI application. The results of this research show that: 1) implementation of P5 at stages: a. planning is carried out by observing problems that occur in the surrounding environment which are adapted to the needs of Pancasila students and school readiness, b. The implementation was carried out by asking stimulating questions and having collaborated with the resource person. c. Evaluation is carried out by looking at the impacts that arise and the achievement of project dimensions and objectives using the assessment rubric that has been created. 2) the obstacles felt by the facilitator team were limited time in compiling modules, conducting environmental observations and observing the development of Pancasila students, lack of funding and resources that could support project implementation. 3) efforts that have been carried out by collaborating with project members in evaluating the environment and observing the development of Pancasila students, asking Pancasila students to prepare tools and materials that will be used and then using infrastructure in turn